UPAYA PENINGKATAN KETERAMPILAN LOMPAT JAUH GAYA JONGKOK DENGAN MODEL BERMAIN BOX TO BOX - Laksono, Argo Dwiyu (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
Students’ skill in doing long jump of squat style was still low, thus it needed to improve. This research that aimed to improve students’ skill of long jump of squat style through Box To Box game model for the fifth graders SD N 2 Sokaraja Kulon academic year of 2014/2015 that contained 37 students; 16 females and 21 males. The techniques of data collection used observation, documentation, and performance assessment. The results showed that through Box To Box game model was able to improve students’ skill of long jump of squat style from pre-cycle to cycle I and cycle II. The students’ skill of long jump of squat style in cycle I showed that the mastery percentage 46% or 17 students. In the cycle, II improved become 89% or 33 students. The data above showed that there was an improvement of students’ long jump skill of squat style which was 43%. The research conclusion was the implementation of Box To Box game model was able to improve students’ skill of long jump of squat style for the fifth graders SD N 2 Sokaraja Kulon.